Ultrastructure and fourier transform infrared spectrum of exopolysaccharide produced by Lactobacillus rhamnosus NBRC 3425 - Emnace, Ivy C. (Annals of Tropical Research, 2020)
In the search for exopolysaccharide (EPS)—producing LAB strains as potential additive for industrial applications, EPS produced by Lactobacillus rhamnosus NBRC 3425 was subjected to partial characterization to provide further information on its structure and composition. The crude EPS was subjected to scanning electron microscopy (SEM), atomic force microscopy (AFM),transmission electron microscopy (TEM) and Fourier transform infrared spectroscopy (FTIR). Results of TEM analysis confirmed that the test organism is an EPS producer due to the presence of an unstained, clear cell wall or halo that surrounds the bacterial cell typical of a capsular EPS. SEM analysis showed that the crude EPS has pores and spaces between particles. Atomic force microscopy (AFM) at a concentration of 10μg per mL revealed spike-shaped lumps with an average size of 17.81±2.89nm. The FTIR spectrum suggested the presence of hydroxyl (OH) groups of carbohydrate and carbonyl group (C=O). Results showed that based on its structural characteristics, such EPS has the potential for use as stabilizer in food products.